Early Initiation of Combination Antiretroviral Therapy in HIV-1–Infected Newborns Can Achieve Sustained Virologic Suppression With Low Frequency of CD4+ T Cells Carrying HIV in Peripheral Blood. (9th June 2014) - Bitnun, Ari; Samson, Lindy; Chun, Tae-Wook; Kakkar, Fatima; Brophy, Jason; Murray, Danielle; Justement, Shawn; Soudeyns, Hugo; Ostrowski, Mario; Mujib, Shariq; Harrigan, P. Richard; Kim, John; et al.
Abstract : We studied a cohort of children initiated on treatment doses of combination antiretroviral therapy within 72 hours of birth. In children who achieved sustained virologic suppression, measures of HIV-1 reservoir size in peripheral blood were very low. Abstract : Background.  A human immunodeficiency virus type 1 (HIV-1)–infected infant started on combination antiretroviral therapy (cART) at 30 hours of life was recently reported to have no detectable plasma viremia after discontinuing cART. The current study investigated the impact of early cART initiation on measures of HIV-1 reservoir size in HIV-1–infected children with sustained virologic suppression. Methods.  Children born to HIV-1–infected mothers and started on cART within 72 hours of birth at 3 Canadian centers were assessed. HIV serology, HIV-1–specific cell-mediated immune responses, plasma viremia, cell-associated HIV-1 DNA and RNA, presence of replication-competent HIV-1, and HLA genotype were determined for HIV-1–infected children with sustained virologic suppression. Results.  Of 136 cART-treated children, 12 were vertically infected (8.8%). In the 4 who achieved sustained virologic suppression, HIV serology, HIV-1–specific cell-mediated immune responses (Gag, Nef), and ultrasensitive viral load were negative. HIV-1 DNA was not detected in enriched CD4 + T cells of the 4 children (<2.6 copies/10 6 CD4 + T cells), whereas HIV-1 RNA was detected (19.5–130 copies/1.5 µg RNA). No virion-associated HIV-1 RNA was detected following mitogenic stimulation of peripheral blood CD4 + T cells (5.4–8.0 million CD4 + T cells) in these 4 children, but replication competent virus was detected by quantitative co-culture involving a higher number of cells in 1 of 2 children tested (0.1 infectious units/10 6 CD4 + T cells). Conclusions.  In perinatally HIV-1–infected newborns, initiation of cART within 72 hours of birth may significantly reduce the size of the HIV-1 reservoirs. Cessation of cART may be necessary to determine whether functional HIV cure can be achieved in such children.